THE ROLE OF THE STUDENTS’ INDEPENDENT WORK IN THE INDIVIDUAL STYLE FORMATION OF THE SELF-REGULATION EDUCATIONAL ACTIVITY - E.V. Lopanova; Vilvijaya, O.L. Osadchuk; D. M. Dreeva; N. Akyeva, L; Sanny, T. Kalabekova (International Journal of Psychosocial Rehabilitation, 2020)
The article reveals the urgency of developing a new approach to managing the students’ independent work on the basis of strengthening their subjective position. The model of managing students’ independent work as a pedagogical system, represented by the interaction of participants in the educational process, is described. A complex of psychological and pedagogical conditions for managing independent work is described, including motivation, differentiation and activation of students’ independent work. The individual style self-regulation selection in educational activity as one of the criteria for the effectiveness of students’ independent work management is justified. The experimental and experimental testing results of the conditions set are presented, which testify to the transition of students from an ineffective style to an effective style of educational activity self-regulation.